PENGARUH MARKET ORIENTATION TERHADAP SERVICE QUALITY, SATISFACTION, DAN LOYALTY PELANGGAN TOKO BUKU GRAMEDIA DI JAWA TIMUR - Subroto, FX Agus (Jurnal Manajemen dan Kewirausahaan, 2013)
The research objectives were to prove and to analyze the effect of market orientation on service quality, customer satisfaction and loyalty. The research sample consisted of 144 customers. The data were analyzed using Structural Equation Modeling (SEM) with AMOS. The results proved that market orientation had significant effect on service quality; market orientation had significant effect on satisfaction; market orienta-tion had no significant effect on customer loyalty; service quality had significant effect on satisfaction; service quality had no significant effect on customer loyalty. Customer satisfaction had significant effect on customer loyalty.